2014
DOI: 10.4172/2161-0959.1000180
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Duration of using Superabsorbent Diaper on the Incidence of Urinary Tract Infection in Children

Abstract: Background: UTI is a common infection in children. Its highest prevalence takes place during infancy and toilet training period in which most infants use diaper. However, the impact of diaper use on UTI in children has been conflicting. Objective: To determine the correlation between duration of superabsorbent diaper usage with incidence of UTI in children. Methods: We performed a prospective cohort study from August-September 2011. We recruited children who used diaper every day, went to play group or posyand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
2
0
1
Order By: Relevance
“…Lestari et al themselves found that use of disposable diapers >4 hours (mean subjects used >12 hours) increased UTI 2.89 times compared to using diapers <4 hours (Tri Puji Lestari, 2014) The prevalence of pathological phimosis in children at H. Adam Malik Hospital Medan in this study was 47.2% and prevalence of physiological phimosis was 52.8%. Phimosis is a clinical condition in which foreskin cannot be retracted so that glans is not visible.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…Lestari et al themselves found that use of disposable diapers >4 hours (mean subjects used >12 hours) increased UTI 2.89 times compared to using diapers <4 hours (Tri Puji Lestari, 2014) The prevalence of pathological phimosis in children at H. Adam Malik Hospital Medan in this study was 47.2% and prevalence of physiological phimosis was 52.8%. Phimosis is a clinical condition in which foreskin cannot be retracted so that glans is not visible.…”
Section: Discussionmentioning
confidence: 44%
“…The use of disposable diapers in children is a trend nowadays because it is considered practical as compared to cloth diapers. Indonesia represents fourth largest consumer after China, India and the United States (Tri Puji Lestari, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Faktor resiko infeksi saluran kemih pada anak berbeda menurut kelompok umur. Faktor resiko infeksi saluran kemih pada anak usia 2-24 bulan menurut penelitian Lestari et al (2014) yaitu penggunaan popok daya serap tinggi >4 jam perhari terutama pada anMenurut IDAI (2011), infeksi saluran kemih pada saat bayi dan anak akan mengakibatkan dampak dikemudian hari hingga jangka panjang terhadap fungsi ginjal yaitu mengakibatkan gagal ginjal akut, bakteremia, dan sepsis. Komplikasi infeksi saluran kemih jangka panjang adalah parut ginjal, hipertensi, dan gagal ginjal.…”
Section: Pendahuluanunclassified